Operator algebras and their applications : a tribute to Richard V. Kadison : AMS Special Session, January 10-11, 2015, San Antonio, Texas - Kadison, Richard V., 1925-; Doran, Robert S., 1937-; Park, Efton (Contemporary mathematics (American Mathematical Society), 2016)
This volume contains the proceedings of the AMS Special Session Operator Algebras and Their Applications: A Tribute to Richard V. Kadison, held from January 10-11, 2015, in San Antonio, Texas. Richard V. Kadison has been a towering figure in the study of operator algebras for more than 65 years. His research and leadership in the field have been fundamental in the development of the subject, and his influence continues to be felt though his work and the work of his many students, collaborators, and mentees. Among the topics addressed in this volume are the Kadison-Kaplanksy conjecture, classif.